PENGARUH KOMITMEN ORGANISASI, MOTIVASI, KOMPETENSI, KOMPENSASI, DAN PEMANFAATAN TEKNOLOGI INFORMASI TERHADAP KINERJA MANAJERIAL PADA PT. POS INDONESIA (PERSERO) CABANG PEKANBARU - Rahmayanti, Wella; Alfiati, Alfiati; L, Al Azhar (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2019)
Competition in the business world at the present time is felt very tight, thereforecompanies are expected to have strong capabilities in various fields such as informationtechnology, finance, marketing, operations, and human resources and service quality.Various business units must compete to improve the quality and quantity they have inorder to survive. To continue to improve the quality and quantity of PT Pos Indonesia(Persero) which has been established and operates for a long time to be able to monitorall its operational activities, especially in managerial performance. This study aims toexamine the effect of organizational commitment, motivation, competence, compensation,and utilization of information technology on managerial performance at PT. PosIndonesia (Persero) Pekanbaru Branch. This research was conducted by questionnairesurvey method for managers and supervisors. The sample of this study was 51respondents who were involved in managerial activities and processed using the SPSS 22application. The data analysis method used in this study was multiple linear regressionanalysis. The results of this study indicate that organizational commitment, competence,compensation have no effect on managerial performance. While the motivation andutilization of information technology affect managerial performanceKeywords : Managerial Performance, Organizational Commitment, Motivation,Competence, Compensation, Use of Information Technology.